AN ANALYSIS OF FEMINISM IN SYLVIA PLATH’S POEMS (THE CONTENT ANALYSIS OF GENERAL MEANING, DETAILED MEANING AND INTENTION) - Indah Damayanti; Hendra .; Ina Rohiyatussakinah (Journal of English Language Teaching and Literature (JELTL), 2019)
This research is aimed to know meaning and Feminism in Sylvia Plath’s Poems. The objectives of this research were to find out the general meaning and detailed meaning and to find out kinds of feminism in poems. This research used qualitative descriptive method using content analysis as the research method. This research used reading and taking note as collecting the data, and technique of analysis data in this research are reading the whole poems, interpreting poems, and making the conclusion. The data source of this research were taken from Sylvia Plath’s poems, they are; Daddy, Lady Lazarus, and Last word. The result of this research were findings showed that there were 64 data contained, 59 data in general meaning and detailed meaning in poems and there were 5 data in kinds of feminism in poems. This research concluded the kinds of feminism, they are Liberal Feminism, Radical Feminism, Psychoanalytic Feminism, Marxist Feminism, Socialist Feminism, Multicultural Feminism, Eco feminism, and Postmodern feminism, this research also concluded the kinds of feminism in the poems, they are; poem Daddy (Radical feminism, Marxist feminism, Socialist feminism), poem Lady Lazarus (Marxist feminism), poem Last word (Marxist feminism).